The Importance of Clinical Records and Expert Reports in Insurance Medicine: From Prediction to Provision - Henrique Durão, Carlos (Gazeta Médica, 2024)
This article aims to raise awareness about the proper completion of medical records in the clinical process, discussing the various medico-legal repercussions that this information represents not only in the clinical evolution, but also in the medical-legal documentation that it represents in Court when assessing the Criminal Law, Labor Law, Civil Law, among others.